PARTISIPASI MASYARAKAT DALAM PELAKSANAAN MUSYAWARAH RENCANA PEMBANGUNAN DESA DI DESA TITIAN MODANG KOPAH KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2017 - Perdana, Muhammad Firman; Laksmono, Bambang Shergi; Harto, Syafri; Ismandianto, Ismandianto (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2019)
Village as a government that directly related to the community is the main focus in government development, because most of Indonesia's territory is in the countryside. Therefore, in village development it needs to be directed at the realization of an "independent village". In order to encourage and awaken the ability of the community, especially rural communities, many programs have been made by the government. One of them is through empowering rural communities by involving the community and elements of government that have more reactive development policies that give priority to the needs of village communities in budget allocation so that they are able to exploit the potential of their respective regions. This study aims to determine: 1) community participation in the implementation of Musrenbang Desa in Titian Modang Kopah Village, Kuantan Tengah District, Kuantan Singingi District; and 2) know the obstacles. Meanwhile, the research method used is qualitative research with a descriptive approach, and data collection techniques through interviews, observation and documentation. The results of this study concluded that: 1) The level of community participation in the Musrenbangdes was very lacking, so the Musrenbangdes implementation activities in Titian Modang Kopah Village were only a formality; and 2) The obstacle in the implementation of the Musrenbangdes in Titian Modang Kopah Village is the difficulty in making decisions regarding the prioritized program which has not been realized, the community is less able to express their aspirations because they still have weak analytical power to the development needs due to weak resource factors the community and the lack of synergy between the various development funding sources owned by Titian Modang Kopah Village. As a consequence of these obstacles, many government programs are not based on the potentials and uniqueness of the Region, causing many potential in Titian Modang Kopah is ineffective.